Analisis Kelembagaan dan Peranannya terhadap Pendapatan Peternak di Kelompok Tani Simpay Tampomas Kabupaten Sumedang Provinsi Jawa Barat (Studi Kasus di Kelompok Peternak Kambing Simpay Tampomas Kecamatan Cimalaka Sumedang) - Siswoyo, H.; Setyono, D. J.; Fuah, A. M. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2013)
A survey study had been carried out in Cimalaka of Sumedang district, West Java. The objectives of the study were to analyze the institutional capacity of the Simpay Tampomas dairy goat farmers group and to understand  the group roles increasing farmers income from dairy goat enterprises. The method used in this study included work performance analysis by using Likert scale, income analysis, and Rank Spearman correlation. Intercorrelated variables in this study included farmers income with organizational experience, business experience, and business scale.  Seventeen farmers of Simpay Tampomas group were interviewed using questionnaires that has been provided.  The results showed that farmer group was effective with the effectiveness value of 390. The Correlation between income with business scale was very strong indicated by the value of correlation coefficient of 0.722, while the correlation between income and organizational experience was -0.151. The results suggested that there was no correlation between farmers income and organizational experiences as well as between income and business experiences.  The condition was relatively due to the difficulties of farmers in adopting new technology and implementating effective management in goat farming.